Місце незалежної української держави в геополітичних проектах C. Л. Рудницького - Окладна, Марина Георгіївна; Перевалова, Людмила Вікторівна (Право, 2017)
У статті розглянуті основні геополітичні ідеї відомого українського вченого С. Рудницького, які є важливішою складовою частиною української соціально-політичної думки першої половини ХХ ст., обґрунтовується їх актуальність у контексті внутрішньої та зовнішньої політики України. Автори аналізують геополітичну концепцію вченого про створення Балтійсько-Чорноморської федерації та її значення для визначення сучасних пріоритетів української держави.

The article is devoted to the geopolitical ideas of famous ukrainian scientist Stepan Rudnitsky. His scientific activity on problems of geography, history, political science, ethnography are relevant today for formation of national identity of Ukrainians, consciousness of its role and place in European process of democratic transformation. In his work, the scientist informed the world about Ukrainian problems, in the solution of which must be involved all countries of Western Europe and the world. The events of recent years confirmed relevance of his ideas, which he shared with us in the beginning of XX century. In the article authors analyze geopolitical concepts of Ukrainian scientist, justify relevance of his ideas, which deals with domestic and foreign policy of Ukraine.
The place of the independent Ukrainian state in the geopolitical projects of S. L. Rudnytsky
Keywords: геополітика; Рудницький С.; суверенітет; незалежність; національна держава; право націй на самовизначення; федерація; націоналізм; geopolitics; Rudnitsky S.; sovereignty; independence; national government; right of nations to self-determination; federation; nationalism